The role of vacuum circuit breakers in traction substations - Juraeva Kamila Komilovna; Rustemova Aynura Rustemovna (International Journal on Orange Technologies, 2020)
This paper investigates major points of the role of vacuum circuit breakers in traction substations. Therefore, research has been analyzed both analytical and theoretical aspects of the circuit breakers in traction cases. In conclusion, research has been pinpointed outcomes and shortcomings of the vacuum circuit breakers in traction substations.